INFLUENCE OF PRODUCT PACKAGING ATTRIBUTES ON CHOICE OF DETERGENTS PURCHASED BY CONSUMERS IN NAKURU COUNTY, KENYA - KARANI, LUCYANN MUTHONI (KABARAK UNIVERSITY, 2016)
With the growing liberization of trade and business in Kenya, many manufacturing firms are now able to produce and bring to the markets broad varieties of products. On the other hand consumers have become more knowledgeable and are seeking lot of information before purchase and consumption of products and services. In detergent market particularly, manufacturers are nowadays increased due to the level of increased demand for detergents induced by the improved lifestyles of the consumers, such that competition has become more stiff. For these reasons the firms are now putting more effort in mode of packaging of their products. Therefore, the study intended to empirically examine the influence of packaging attributes on detergent choice by the consumers in Nakuru. In achieving this general objective the study sought to examine the extent to which colour of the package, material of the package, size of the package and package label influences consumers‘ choice of the detergent. Structured questionnaire was be used to gather primary data from various consumers in Nakuru. Study sample size was 222 consumers, which was being selected using a multistage sampling which entailed stratified random and convenience sampling. Multiple regression analysis was used to test the relationship between variables under study whereas spearmans correlation was used to test research hypotheses at 0.05 significant levels. The study findings were presented using frequencies distribution tables and percentages. The finding of the study shown that Colour of the package had a significant influence consumer choice which had a p- value of (0.000) which is less than alpha 0.05.Packaging material had no significant influence on consumer choice(p=0.067) which is greater than alpha 0.05.Size of the packaging had no significant influence on detergent consumer choice(p=0.664) which is greater than (alpha 0.05).packaging label had significant influence on consumer choice (p=0.006) which is less than (alpha 0.05).The results are expected to give insight to detergent manufacturer and marketers in improving product presentation. Attributes of packaging contributes only 32% of the consumer choice of the detergent. There is need for further research to identify other variables that affect consumer choice that would contribute to the 68% not accounted for by this study. There is need for further research to identify other variables that affect consumer choice of the detergents that would contribute to the 68% not accounted for by this study. The study also contributed to the existing knowledge in aiding scholars understand the influence the packaging attributes has on consumer choice thus forming their basis for further research.
FULL TEXT
Keywords: product packaging attributes, consumer choice, packaging colour, packaging quality of material, packaging size variety, packaging label